Moodle tools for teaching foreign languages at distance learning department - Oksana O. Kandrashkina; Elena V. Revina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper investigates the use of the Moodle system tools for teaching the subject of Foreign Languages (English) at the faculty of distance and part-time education of the Institute of Oil and Gas Technologies (INGT) of Samara State Technical University (SSTU). The analysis was carried out on the content material of Moodle electronic course for the specialty Petroleum engineering 21.03.01, 2020-2021 years. The course structure, tools for presenting educational material for practical classes and independent work, as well as assessment tools for intermediate and final monitoring control were analyzed. The study showed that the content of the course is presented logically and divided into modules in accordance with the main educational program and the Federal State Educational Standard of the Russian Federation. The Page tool was chosen to present the material for practical classes, which ensures the availability and clarity of educational material provided. Tasks for independent work and study are implemented via the Task tool in such a way that the files can be downloaded, then done and uploaded to the system. The effectiveness of the course was analyzed according to the data automatically provided by the system. The following aspects were taken into consideration: online activity of students in the system, the number of downloaded and completed assignments, the number of attempts to take tests, assessment reports based on the results of students` performance. The study has shown that the tools chosen for the course are relevant and provide effective learning. Analysis of program data has suggested that materials and exercises are easily accessible and system navigation has not caused any difficulties for students. Thus, it can be concluded that the Moodle system has proved to be an effective platform for distance learning of part-time students with a low level of language proficiency.